Cardiac events in world-class athletes: An internet-based study - Lahaye, S. L. D.; Cunuder, A. L.; Lachard, T.; Menard, V.; Lhuissier, F.; Dupont, A. C.; Wurtz, A. S.; Marblé, C.; Francois, C.; Schnell, F. (Medicine & Science in Sports & Exercise, 2022)
Purpose This study aimed at assessing the prevalence of adverse cardiac events, as identified in the media, in world-class athletes according to their sex and sports discipline.